The Implementation of Service Quality, Perception of Price, Location Towards Purchasing Decisions (Case Study of Coffee Shops in North Bekasi) - Rini Wijayaningsih; Andrian (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to ascertain how price perception, location, and service quality affect customers' decisions to buy from Identiq Coffee Shop. This kind of study is quantitative in nature. This study's population is unknown. Purposive sampling combined with non-probability sampling is a sampling strategy. There were 96 responders in the study's sample. methods for gathering data by sending out surveys with Google Form. Multiple Linear Regression analysis was used in this work to test hypotheses. A number of coffee shops in North Bekasi are the topic of the study. The study's findings show that the factors of location, price perception, and service quality all significantly and concurrently positively affect the purchasing decision variable.